Peace, Conflict and Resolution (Good vs. Evil) - Hossain, Arif (Bangladesh Journal of Bioethics, 2013)
The immense structural inequalities of the global social /political economy can no longer be contained through consensual mechanisms of state control. The ruling classes have lost legitimacy; we are witnessing a breakdown of ruling-class hegemony on a world scale. There is good and evil among mankind; thus it necessitates the conflict between the good and evil on Earth. We are in for a period of major conflicts and great upheavals. It's generally regarded that Mencius (c.371- c.289 B.C) a student of Confucianism developed his entire philosophy from two basic propositions: the first, that Man's original nature is good; and the second, that Man's original nature becomes evil when his wishes are not fulfilled. What is good and what is evil? Philosophers of all ages have thought over this question. Each reckoned that he had solved the question once and for all, yet within a few years the problem would re-emerge with new dimensions. Repeated acts of corruption and evil action makes a man corrupt and takes away a man from his original nature. Still now majority of the people of the world give compliance to corruption because of social pressures, economic pressures, cultural pressures and political pressures. The conflict between good and evil is ancient on earth and is prevalent to this day. May be the final confrontation between the descendants of Cain and Abel is at our doorsteps. During the 2nd World War America with its European allies went into world wide military campaign to defeat Germany, Italy and Japan. When the Second World War ended in 1945 the United States of America came out as victorious. America was the first country to detonate atomic bomb in another country. During that period Russia fell into competition with America in politically colonizing countries after countries. With the fall of Communism Russia terminated its desire wanting to be the champion of the oppressed of the world. The situation in Russia continues to deteriorate, a country which until only a few years ago was a superpower. Russians are deeply disillusioned today with the new politicians in Russia, who they says "promise everything and give nothing." The Russians still strongly oppose a world order dominated by the United States. If anyone looks at or investigates the situations in other countries it can be seen that at present almost all countries of the world are similar or same in the forms of structures of corruption and evil. The Worldwide control of humanitys economic, social and political activities is under the helm of US corporate and military power. The US has established its control over 191 governments which are members of the United Nations. The last head of state of the former Soviet Union, Mikhail Gorbachev on December 2012, at a conference on the future of the Middle East and the Black Sea region in the Turkish city of Istanbul, has warned the US of an imminent Soviet-like collapse if Washington persists with its hegemonic policies. Mass public protest occurred against US hegemony are mainly from Muslim countries of South East Asia, South Asia, Central Asia, West Asia, North Africa and Africa. The latest mass protests erupted in September 2012 when the divine Prophet Muhammad (pbuh) was insulted by America and Israel. There were strong mass protests by people from Indonesia to Morocco and in the European countries by mostly immigrants and Australia were there are Muslim populations. This worldwide protest had occurred while the rise of the masses is ongoing against corrupt rulers in West Asia and North Africa. The masses of the people are thirsty and desperate for justice, dignity, economic welfare and human rights. Most major religions have their own sources of information on the Last Age of Mankind or the End of Times, which often include fateful battles between the forces of good and evil and cataclysmic natural disasters. Humans are evolving to a final stage of their evolution towards a 'New Age that is to come which the corrupt does not understand. At present times a final battle of good versus evil on Earth will ensue. The World powers (leaders) and their entourages who are really detached from the masses have organized to keep aloft the present world order that degenerates the masses in corruption, keeps the people in unhappiness, and deprives the masses from economic well being, education and keeps promoting wars and conflicts to support corruption and evil. We are at the ?End of Times?. The Promised Messiah will come to set right what is wrong, no doubt. DOI: http://dx.doi.org/10.3329/bioethics.v4i1.14264 Bangladesh Journal of Bioethics 2013; 4(1):9-19